The impact of cognitive impairment on self-management in chronic obstructive pulmonary disease: A systematic review - Baird, Chelsea; Lovell, Janaka; Johnson, Marilyn; Shiell, Kerrie; Ibrahim, Joseph E. (Respiratory medicine, 2017)
To determine the characteristics of persons with cognitive impairment being able to self-manage in chronic obstructive pulmonary disease (COPD). In accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidance this systematic review examined all studies in English from 1st January 2000 to 20 February 2016, describing the relationship between cognition and COPD self-management domains in older community dwelling persons with dementia or cognitive impairment. Of 4474 studies identified, thirteen studies were eligible for inclusion. No studies differentiated populations into recognized dementia subtypes. Study aims were variable; most (n = 7) examined inhaler competency alone. Studies identified a link between worsening cognition and the need for assistance in activities of daily living. Only one study evaluated the impact of cognition on overall self-management and found no association between cognitive impairment and self-rated self-management. Mild degrees of cognitive impairment were associated with reduced symptom recall. Cognitive impairment in COPD was associated with high degrees of inhaler incompetency. Basic cognitive screening tests were able to predict inhaler incompetence with reduced overall cognitive function, dyspraxia, and/or executive function identified as predictors of incompetency. Multiple measures of disability consistently demonstrated that cognitive impairment in COPD significantly increased the need for assistance in many aspects of daily living, treatment adherence, and effective self-management. Given the nature of neuropsychological deficits seen in COPD, dedicated screening tools are required. Future research should investigate the impact of cognitive dysfunction in COPD and identify how to support those that lack capacity to self-manage. •Cognitive impairment in COPD significantly increases the need for assistance in many aspects of daily living.•Reduced overall cognition, dyspraxia, and/or executive dysfunction are associated an inability to self-administer inhalers.•Basic cognitive screening tests were readily able to predict inhaler incompetence.•The current GOLD guidelines do not take cognitive abilities into account.•An understanding of the patient’s cognitive function may identify barriers to effective self-management.